Overpressure-generating Mechanisms in the Blok F3, North Sea, Netherland - Karin*, Khusmia; Sudarmaji, Sudarmaji (Aceh International Journal of Science and Technology, 2021)
Block F3 North Sea is a block with pore pressure values that vary over time due to complex geological conditions such as burial and various sedimentation zones. Pore pressure is one of the important aspects that need to be analyzed as a basis for the identification of zones and overpressure mechanisms. Overpressure is a greater pore pressure condition than normal pressure and may cause drilling problems, such as kicks, blowouts, etc. This study calculated pore pressure values using the eaton method approach with well data and seismic data. Both data are integrated for generating pore pressure values in 1D and 3D. 1D Modelling uses Interactive Petrophysics 3.5, while 3D modeling uses Petrel software. In 3D modeling, the variables used are interval velocity and inversion velocity obtained by acoustic impedance inversion. The sub-variables used are the inversion density and the regression density obtained from well density acoustic impedance inversion. The existence of a 1D overpressure zone at a depth of 1,100 1,800 m with an overpressure value of 3,836 18,975 kPa. In addition, the overpressure value based on the 3D model is 8,000 18,000 kPa. The overpressure zone is validated using an acoustic impedance inversion model with a high value of 5,200 5,380 (m/s)*(gr/cc). Overpressure in Block F3 is predicted to occur from disequilibrium compaction.